Effectiveness of mathematics education in secondary schools to meet the local universities missions in producing quality engineering and science undergraduates - Hasan A.B.; Abdul A.F.; Selamat Z. (Institute of Physics Publishing, 2024)
Critical claims by certain quarters that our local undergraduates are not performing well in Mathematics, Statistics and Numerical Methods needs a serious thinking and actions. Yearly examinations results from the Sijil Pelajaran Malaysia (SPM equivalent to A-Level) and Sijil Tinggi Pelajaran Malaysia (STPM equivalent to O-Level) levels have been splendid whereby it is either increasing or decreasing in a very tight range. A good foundation in mathematics and additional mathematics will tremendously benefit these students when they enter their university education especially in engineering and science courses. This paper uses SPM results as the primary data, questionnaires as secondary, and apply the Fish Bones technique for analysis. The outcome shows that there is a clear correlation between the causes and effect.